The impact of Measles-Rubella vaccination on the morbidity and mortality from Congenital Rubella Syndrome in 92 countries - Emilia Vynnycky; Timoleon Papadopoulos; Konstantinos Angelis (Taylor & Francis Group, 2019)
Since 2011, GAVI, The Vaccine Alliance, has funded eligible countries to introduce rubella-containing vaccination (RCV) into their national schedule. Two key indicators used to monitor the impact - the future deaths and DALYs (Disability Adjusted Life Years) averted through vaccination conducted in specific periods - are poorly understood for rubella and Congenital Rubella Syndrome (CRS). We calculate these indicators using an age-structured dynamic transmission model for rubella, with historical vaccination coverage projections during 2001-30 in 92 low and middle-income countries considered most likely to require global support to achieve the Global Vaccine Action Plan's objectives. 131,000 CRS deaths and 12.5 million DALYs may be prevented with immunization campaigns at best-estimate coverage during 2001-30, relative to those without additional support. The impact depended on the time period considered and the method for attributing deaths averted to vaccination in specific periods. The analyses support ongoing activities to reduce CRS-related morbidity and mortality.